Menemukan Identitas: Perjalanan Adaptasi Muallaf dalam Menjalani Kehidupan Baru - Tiara Emelisa; Nesca Anggesti (UIN Fatmawati Sukarno Bengkulu, 2024)
This research aims to explain finding the identity of a convert's adaptation journey in living a new life. According to Zakiyah Daradjat, religion in the lives of converts is a system consisting of religious awareness and religious experience, in converts the religion they adhere to is a system and experience and awareness in religion. The research method uses literature study, by analyzing 25 journals as primary data. Data analysis in several stages, the first stage determines the theme, the second stage selects journal articles that are relevant to the theme and in accordance with the deadline of the last 11 years, the third stage is a review process of 7 journal articles. The results of this research show that the adaptation of a convert to the local environment It is very important to establish a harmonious relationship with the local community.